Sternal pore plates (glandular areas) of male Thripidae (Thysanoptera) - Mound, Laurence A. (Zootaxa, 2009)
Variation is illustrated in the specialized areas known as pore plates (glandular areas or areae porosae) that occur on the sternites of males of many Thysanoptera species, and the occurrence of these structures in genera of Thripidae is tabulated. Pore plates are present in more than 60% of genera in this family, and known to be absent in about 20%; males are not known in a further 20% of the genera. In families of Terebrantia other than Thripidae, pore plates also occur in Fauriellidae, Heterothripidae and Adiheterothripidae, but not in Aeolothripidae, Melanthripidae and Uzelothripidae. Females in a very few species of Thripidae have pore plates apparently similar to those of males.